2021
DOI: 10.5435/jaaosglobal-d-21-00101
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy Proven Focal Osteolysis in a Stainless-Steel Limb-Lengthening Device: A Report of Three Cases

Abstract: Three pediatric patients presented with histologically confirmed osteolysis after limb lengthening with a magnetic, telescoping, stainless-steel device. The first patient's findings were discovered radiographically before routine removal of the device. In all cases, intraoperative histologic specimens taken from around the modular junction demonstrated particle-laden macrophages with suspicion for metal debris. Silicone debris was also identified. We found definitive osteolysis secondary to metal at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…A similar report by Frommer et al [ 20 ] identified osteolytic changes in 20 of the 57 (35%) implanted nails at a mean 9.5 months after index lengthening surgery. They also found macroscopic corrosion at the modular junction in 83% of recipients, similar to that reported by our group in a previous publication [ 19 ] and a separate analysis of retrieved nails at another institution [ 30 ]. In a comparative study of multiple variations of an intramedullary limb lengthening nail, Iobst et al [ 29 ] observed a greater proportion of bone abnormalities at the modular junction of the STRYDE nail, as compared to the PRECICE or FITBONE (Orthofix Medical Inc., Lewisville, TX, USA).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A similar report by Frommer et al [ 20 ] identified osteolytic changes in 20 of the 57 (35%) implanted nails at a mean 9.5 months after index lengthening surgery. They also found macroscopic corrosion at the modular junction in 83% of recipients, similar to that reported by our group in a previous publication [ 19 ] and a separate analysis of retrieved nails at another institution [ 30 ]. In a comparative study of multiple variations of an intramedullary limb lengthening nail, Iobst et al [ 29 ] observed a greater proportion of bone abnormalities at the modular junction of the STRYDE nail, as compared to the PRECICE or FITBONE (Orthofix Medical Inc., Lewisville, TX, USA).…”
Section: Discussionsupporting
confidence: 87%
“…The modular components within the stainless-steel intramedullary limb lengthening nail are subject to produce wear particles and a macrophage-driven adverse tissue reaction. Reports of osteolysis between similar designs are largely limited to total hip arthroplasty (THA); though recent reports have suggested this process in intramedullary lengthening nails [ 19 , 20 , 21 , 22 , 23 , 24 ]. We sought to examine the total number of stainless-steel nail recipients for LLD at a single tertiary care center to determine the incidence of adverse tissue reaction before and following routine explantation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations